EVALUASI KEBIJAKAN PENGELOLAAN SWALAYAN DI KOTA PEKANBARU TAHUN 2019-2020 (STUDI KASUS PADA INDOMARET DAN ALFAMART) - Yunny Rachma Wati; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Pekanbaru City Regional Regulation Number 9 of 2014 concerning Management of People's Markets, Shopping Centers and Supermarkets in article 20 paragraph 1 explains that the location of the establishment of shopping centers and supermarkets must refer to the RTRW, RDTRK, including the Pekanbaru City zoning regulations. The purpose of this study is to explain and explore the evaluation of Indomaret and Alfamart supermarket management policies in Pekanbaru City.The theory used in this study is based on 6 policy evaluation indicators from William Dunn, namely effectiveness, efficiency, adequacy, fairness, responsiveness and feasibility. The research method used in this study is a qualitative research method. Data collection techniques through interviews, observations, and documentation studies. The results of this study indicate that the Indomaret and Alfamart supermarket management policies in Pekanbaru City have not achieved the output of the Indomaret and Alfamart supermarket management policies in accordance with their objectives, namely to provide protection, organize and regulate the existence and establishment of people's markets, shopping centers and supermarkets in order to be able to compete globally. healthy, synergistic, mutually reinforcing and mutually beneficial. Keywords: Effectiveness and Efficiency, Adequacy and equity, Responsiveness, Appropriateness